PENGARUH LAYANAN BIMBINGAN KELOMPOK TEKNIK HOMEROOM UNTUK MENINGKATKAN SELF-DISCLOSURE - Alfonsus Dea Novan; Hadi Pranoto; Mudaim (Universitas Muhammadiyah Metro, 2026)
This study aimed to determine whether or not there is an effect of group guidance services homeroom technique to improve the self-disclosure of adolescents of Santo Tarsisius Ngestirahayu. This type of research was conducted with a quantitative approach using the One Group Design Pre-test Post-test research design. In this study, one group of subjects totaling 10 adolescents conducted a pre-test and post-test. The data collection technique used was through filling out the self-disclosure scale by the research subject. The pre-test average value was 61.7000 and the post-test average value was 84.2000. Data analysis was carried out using the Paired Sample T-test test using the help of the SPSS 29.0.2.0 program. The results of the Paired Samples T-test analysis obtained the tscore is greater than the ttable, namely -5.453> 2.262 and Sig. Two-Sided p = 0.001 <0.05, thus, Ha is accepted and Ho is rejected. So it can be concluded that there was an effect of homeroom technique group guidance services to improve adolescent self-disclosure. The implementation of homeroom technique group guidance services is expected to be a more effective approach in helping adolescents improve self-disclosure.